2009
DOI: 10.1103/physrevb.79.235422
|View full text |Cite
|
Sign up to set email alerts
|

Irradiation-enhanced adsorption and trapping ofO2on nanoporous water ice

Abstract: We have found that irradiation with 50-150 keV protons enhances gas adsorption in nanoporous amorphous ice by creating high-energy binding sites. If irradiation is done in vacuum, the ice is compacted and does not adsorb significantly in subsequent exposure to gas. If irradiation occurs while the ice is exposed to an ambient O 2 pressure, adsorption is enhanced by a factor as high as 5.5 compared to unirradiated ice. The maximum concentration of adsorbed O 2 increased with increasing pressure and decreasing io… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 34 publications
(20 reference statements)
0
9
0
Order By: Relevance
“…Similar trapping mechanisms have also been seen experimentally for other volatiles, such as N2, CH4, CO2, O2, NH3; and noble gases, such as Ar, Kr, Xe (Ayotte et al 2001;Notesco, Bar-Nun & Owen 2003;Bar-Nun, Notesco & Owen 2007;Gálvez et al 2008;Shi, Teolis & Baragiola 2009;Fayolle et al 2011;Yokochi et al 2012;Bar-Nun & Laufer 2013;Fresneau et al 2014). It has also been suggested that irradiation of H2O ice may collapse pores in the amorphous structure, thereby further enhancing trapping of volatiles (e.g., Shi, Teolis & Baragiola 2009).…”
Section: Binding Energiesmentioning
confidence: 74%
See 1 more Smart Citation
“…Similar trapping mechanisms have also been seen experimentally for other volatiles, such as N2, CH4, CO2, O2, NH3; and noble gases, such as Ar, Kr, Xe (Ayotte et al 2001;Notesco, Bar-Nun & Owen 2003;Bar-Nun, Notesco & Owen 2007;Gálvez et al 2008;Shi, Teolis & Baragiola 2009;Fayolle et al 2011;Yokochi et al 2012;Bar-Nun & Laufer 2013;Fresneau et al 2014). It has also been suggested that irradiation of H2O ice may collapse pores in the amorphous structure, thereby further enhancing trapping of volatiles (e.g., Shi, Teolis & Baragiola 2009).…”
Section: Binding Energiesmentioning
confidence: 74%
“…It has also been suggested that irradiation of H2O ice may collapse pores in the amorphous structure, thereby further enhancing trapping of volatiles (e.g., Shi, Teolis & Baragiola 2009). Such experimental findings imply that weakly bound volatiles can be preserved in the modelled discs at temperatures that are warmer than their respective thermal desorption regimes.…”
Section: Binding Energiesmentioning
confidence: 99%
“…For residence times above the horizontal line labeled "lifetime against sputtering," a molecule is more likely to be sputtered or photodesorbed along with H 2 O before being thermally desorbed. All data come from Sandford and Allamandola (1993), except for the O 2 , which comes from Shi et al (2007), and the "lifetime against sputtering," which comes from Paranicas et al (2002). tion, and, as discussed later, a laboratory measurement on pure H 2 O might not be applicable at Europa's surface.…”
Section: Atmospheric Modelmentioning
confidence: 99%
“…2 come from Sandford and Allamandola (1993), except for the O 2 curve, which came from Shi et al (2007). There was no data available for SO 2 on H 2 O ice, so we used the SO 2 on SO 2 curve.…”
Section: Atmospheric Modelmentioning
confidence: 99%
See 1 more Smart Citation